Strategi Komunikasi Interpersonal Tour Leader Dalam Meningkatkan Loyalitas Wisatawan (Studi Kinerja Tour Leader Permata Tour Lubuklinggau) - Erwin Rochmansyah; Lisa Adhrianti (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2021)
This study aims to find out how the Interpersonal Communication Strategy of a Permata Tour Lubuklinggau Tour Leader with tourist group participants based on the Marketing mix including Product, Price, Place, Promotion to increase the sense of tourist loyalty. This study uses a qualitative approach, we explore information data in the field through in-depth interview techniques to 6 (six) informants based on their own perceptions, in addition to interviews we also conducted participant observations and other recorded documentation. The problem of this research is the extent to which the Interpersonal Communication Strategy of a Permata Tour Lubuklinggau Tour Leader regarding tourists who only use the services of a Permata Tour travel agency, and we found that there are Tour Leaders who do not master the interpersonal communication process well and their goals towards tourists. Based on these findings, we suggest efforts to optimize the performance of tour leaders to apply the basic concept of Hospitality/Excellent Service to tourists. In addition to these findings, we suggest that all Tour Leaders in leading a group of tourists should have carried out a competent test and have a Tour Leader certification from a tourism institution.